On Resurrected Nuggets and Sphincter Windows: Cultured Meat, Art, and the Discursive Subsumption of Nature. Issue 7 (3rd July 2017) - Jönsson, Erik
ABSTRACT: In this article, I scrutinize three art, design, and architecture projects engaging with "cultured, " or "in vitro, " meat (primarily muscle cells cultured outside of bodies) to illuminate the entanglements of academic and extra-academic environments that have characterized cultured meat's history to date, and the conversations that this technology has spurred. In envisioning new ways of eating, and living, these projects (a book of hypothetical recipes, The In Vitro Meat Cookbook, Catts and Zurr's bioartistic engagements with tissue engineering, and Terreform1's tissue-house prototype "The In Vitro Meat Habitat") illustrate cultural practices thought to be enabled by cell culturing's new applications. Emphasizing such visions and conversations allows me to highlight an inattention to discursive dynamics within research on natures subsumed to industrial production processes (Boyd, Prudham, and Schurman2001 ). But engaging with the "subsumption of nature" framework simultaneously allows me to problematize artistic visions presenting nature as fully malleable.